An Analysis on the Development of Corporate Social Responsibility (CSR) - Sekaran, Srividhya (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Corporate social responsibility is a concept which is integrated by the companies to incorporate social concerns to their planning and operations. CSR is generally, understood as being the way through which a company achieves a balance of economic, environmental and social imperatives. Indian and international companies are creating comprehensive CSR programs that engage every business unit. As businesses grow, it is more important than ever before that they consider their impact on a country’s domestic populace. Realizing the importance of CSR in today’s world this paper aims to analyze briefly on all the aspects of CSR. It highlights different phases and different theories in the development of CSR in India.